Comparison of the Quality of Physical Fitness of Elementary School Students in Cities and Villages based on Geographical Location - Gunawan Gunawan; Tatang Muhtar; Dewi Susilawati (UNIB Press, 2024)
This study aims to investigate differences in the quality of physical fitness of students in cities and villages, which are influenced by geographical location and different daily activities. The research method used was quantitative descriptive with a population and sample of 160 people. The data analysis technique applied is the Mann-Whitney Test. The results showed quantitatively significant differences between the two groups, with the average difference showing that fitness in villages reached 5.42 compared to students in cities. This indicates that the group of students in the village has a higher level of fitness than the group of students in the city. The fitness assessment using the Indonesian Physical Fitness Test (TKJI) category shows that students in the city are in the Medium fitness category, while students in the village are in the Good fitness category. The findings illustrate that more active physical activity in villages may be the cause of the difference. Students in villages tend to have a more active lifestyle, engaging in physical activities such as walking, running, and jumping, while students in cities tend to spend their free time playing with gadgets. In conclusion, the results of this study support the view that geographical factors and daily activities affect students' fitness levels, with implications for TKJI categories that indicate better fitness levels in villages than cities.